PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI): PERKEMBANGAN DAN TANTANGANNYA - Sembiring, Robert K. (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2010)
This paper is about PMRI, the Indonesian version of realistic mathematics education developed in the Netherlands. It is a movement to reform mathematics education in Indonesia. What and why PMRI and the problems and challenges it faces in its development. It began as a small experiment ten years ago, now becomes a national movement.